Community Structure of Phytoplankton in The Waters of Bagek Kembar Mangrove Ecosystem Essential Area, Sekotong, West Lombok - Jamiyyah, Shafro' Khuluq; Japa, Lalu; Ilhamdi, Mohammad Liwa (Jurnal Biologi Tropis, 2025)
The Bagek Kembar Essential Ecosystem Area (EEA) is one of the mangrove forest areas in Lombok Island. This mangrove forest area is managed and developed into an educational tourist attraction (Ecotourism) to know various types of mangroves. The existence of Bagek Kembar mangrove Ecotourism is very important to support the economic income of the surrounding community. The existence of these various activities will potentially affect the balance of the mangrove ecosystem and the biota that live in there. This study aims to determine the composition of phytoplankton species and the condition of their diversity in the waters of the Bagek Kembar Mangrove Essential Ecosystem Area, West Lombok. Descriptive exploratory research was the methodology used. A 20 µm plankton net was used to filter 100 L of water in order to sample phytoplankton. Formalin at a 4% concentration was then used to preserve the filtered water samples. Individual abundance, evenness, dominance, and the index of species diversity were computed in order to analyze the data. The findings revealed that there were five divisions and 84 phytoplankton species. The Bagek Kembar Mangrove Essential Ecosystem Area's waters had an average phytoplankton abundance of 2,770 ind/L. The species dominance index of phytoplankton was 0.192 (low category), the species evenness index of phytoplankton was 0.633 (evenly distributed), and the average phytoplankton species diversity index of 2.296 was categorized as moderate. According to the findings of this study, the phytoplankton community's stability in the waters of the Bagek Kembar Mangrove Essential Ecosystem Area fell into the medium range.